Program pelatihan hasta karya sebagai upaya pemberdayaan dan peningkatan ekonomi masyarakat di Desa Purbayan, Baki, Sukoharjo - Nesti Rahmawati Trisnanda; Heri Kusmariyanto; Ardo Muhamad Richard; Endang Masitoh Wahyuningsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
Purbayan Village is located in Baki District, Sukoharjo Regency. As a result of the Covid-19 pandemic, several residents of Purbayan Village have been laid off. These residents lost their jobs and experienced economic difficulties. Therefore, it is necessary to empower the community in Purbayan Village to improve the community's economy. Community empowerment is carried out by craft training of making mask connectors from beads. This activity is expected to improve the economy and the welfare of the community. The method of this activity uses the lecture method and the demonstration method. This activity involved the community, especially PKK women from RT 01 RW 07 Pandeyan, Purbayan Village, Sukoharjo Regency. The results of this activity indicate that the level of achievement of the objectives of this service activity is very good, with an increase in the knowledge and skills of the participants. After the training, participants understand how to make mask connectors and can practice them independently and sell them. The proceeds from the sale of this mask connector are able to increase the income of the people of Purbayan Village.